A Progressive Approach to Teaching Analytics in the Marketing Curriculum. Issue 1 (2nd January 2018) - Liu, Yiyuan; Levin, Michael A.
Abstract : With the emerging use of analytics tools and methodologies in marketing, marketing educators have provided students training and experiences beyond the soft skills associated with understanding consumer behavior. Previous studies have only discussed how to apply analytics in course designs, tools, and related practices. However, there is a lack of study on the practice of teaching analytics systematically in the marketing curriculum. This article fills the gap by introducing a progressive approach to teaching analytics across different marketing courses by focusing on program-wide curriculum mapping and design. We delineate the framework to develop the curriculum with an analytics component.